Restoring Christ's church: John a Lasco and the Forma ac ratio - Springer, Michael Stephen (St. Andrews studies in Reformation history, 2007)
Introduction -- Christ's true church : the Protestant search for unity -- John a Lasco and the London Strangers' Church : the origins and development of the forma ac ratio -- Ecclesiastical administration and the London Strangers' Church -- John a Lascos public ministry -- Ecclesiastical discipline in the forma ac ratio -- The forma ac ratio in Europe -- Conclusion: Lascos legacy